Dermal CD207-negative migratory dendritic cells are fully competent to prime protective, skin homing cytotoxic T-lymphocyte responses - Hain, Tobias; Mahnke, Karsten; Silva-Vilches, Cinthia (The journal of investigative dermatology, 2019)
Dendritic cells (DCs) are important inducers and regulators of T-cell responses. They are able to activate and modulate the differentiation of CD4+ and CD8+ T cells. In the skin, there are at least five phenotypically distinct DC subpopulations that can be distinguished by differential expression of the cell surface markers CD207, CD103, and CD11b. Previous studies have suggested that dermal CD11b−CD207+ conventional type 1 DCs are indispensable for the priming of a skin homing cytotoxic T-lymphocyte response. However, conventional type 1 DCs are also the only skin DC subset capable of cross-presenting exogenous antigens on major histocompatibility complex class I. Thus, it remained unclear whether for antigens that do not require cross-presentation, such as viruses that infect DCs, other DC subtypes in the skin can contribute to cytotoxic T-lymphocyte priming. To address this question, we used a transgenic mouse model that allows inducible expression and presentation of a model antigen on selected subsets of dermal DCs. We show that for antigens presented via the conventional major histocompatibility complex class I presentation pathway, CD207- dermal DCs are fully competent to prime a skin homing cytotoxic T-lymphocyte response that is capable of protection against a local virus challenge and gives rise to skin resident memory CD8+ T cells.
corrected proof published online 16 November 2018
Gesehen am 03.04.2019